2012
DOI: 10.1210/jc.2011-1882
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Thyroid Remnant Ablation Using Repeated Low 131-Iodine Activities (740 MBq/20 mCi × 2) in Patients with Low-Risk Differentiated Thyroid Cancer

Abstract: The Minidose outpatient ablation protocol is effective and diagnostically useful in low-risk DTC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Indeed, postoperative serum Tg value is strongly dependent on the type of determination (stimulated or nonstimulated), type of stimulation (rh-TSH vs. endogenous hypothyroid stimulation), the actual level of TSH stimulation and the volume of remnant thyroid tissue. Therefore, the level of postoperative Tg cannot alone guide the decision for or against RAI administration [29,30,34]. It appears that the postoperative serum Tg value will be more helpful in identifying patients that will benefit from RAI ablation rather than in identifying patients that do not require ablation [4].…”
Section: Does Surgical Pathology Provide Reliable Information For Manmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, postoperative serum Tg value is strongly dependent on the type of determination (stimulated or nonstimulated), type of stimulation (rh-TSH vs. endogenous hypothyroid stimulation), the actual level of TSH stimulation and the volume of remnant thyroid tissue. Therefore, the level of postoperative Tg cannot alone guide the decision for or against RAI administration [29,30,34]. It appears that the postoperative serum Tg value will be more helpful in identifying patients that will benefit from RAI ablation rather than in identifying patients that do not require ablation [4].…”
Section: Does Surgical Pathology Provide Reliable Information For Manmentioning
confidence: 99%
“…At least 12 prospective studies have shown that an activity of 1110 MBq/30 mCi met certain arbitrary endpoints roughly as effectively as the historically often-used 3700 MBq/ 100 mCi, provided the size of the post-surgically remaining tissue Bremnant^is not too large [49]. A few papers have even reported similar ablation rates using ∼20 mCi [34,50], while in contrast, some report a significantly lower ablation rate at 30 mCi than when using 100 mCi. Most importantly, for patients ≥ 45 years, the rate of disease recurrence and DTCspecific mortality was found in some studies to be significantly higher in patients treated with lower RAI activity (≤2000 MBq or 54 mCi), as compared to higher ablative RAI activities [5].…”
Section: Does Adjuvant or Therapeutic Rai Administration Improve Clinmentioning
confidence: 99%
“…Numerous published comparisons [4, 916] have confirmed that rhTSH-aided ablation achieves high remnant eradication rates that are not statistically inferior to those attained with THW-assisted ablation. At the same time, relative to THW, rhTSH use avoids hypothyroid morbidity, improving patient quality-of-life [4, 14, 15, 17–19].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to THW, rhTSH use also lessens extra-thyroidal radiation exposure [20, 21], improving safety [22]. Additionally, a number of published comparisons have documented statistically not different, modest DTC recurrence rates after rhTSH- or THW-aided ablation [911, 14, 16, 23]. rhTSH has a relatively high acquisition cost.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have confirmed that administration of radioiodine for remnant ablation after recombinant human thyroid-stimulating hormone (rhTSH) therapy achieves results that are good and by no means inferior to the traditional way of preparing patients, i.e. by thyroid hormone withdrawal (THW) [3,4,5,6,7,8,9,10,11]. For this reason, most national and society guidelines do not distinguish between rhTSH or THW for the preparation of DTC patients for ablation, except for those with proven distant metastatic disease [2,12,13].…”
Section: Introductionmentioning
confidence: 99%